Phytochemical study of certain gazania species cultivated in egypt - El Kady, Wafaa Mostafa Hussain; El-Shanawany, Mohamed Ahmed Prof. Dr.; Haggag, Eman Gaber Prof. Dr.; Desoukey, Samar Yehia Prof. Dr. (2009)
The genus Gazania belonging to family Asteraceae which is a medicinally important family; its species are flowering ornamental plant native to South Africa
(3GdLRGfjG gh LfS fHGJi jJHY GdYGFdI GdeQcHI hgPg GdYGFdI JYQa HCgejJgG ceUOQ ddfHGJGJ GdWHjI, hgi CMO CfhGY GdfHGJGJ GdeRgQI hehWfgG GdCUdi LfhH CaQjbjG(B.s
Thesis (Phd.)-Helwan university,faculty of pharmacy, department of pharmacognosy, 2015.
Includes of bibliographical references and index.
Keywords: Phytochemical; Biological